ENHANCEMENT IN EFFECTIVENESS OF ANTAGONISTIC MICROBE BY MEANS OF MICROBIAL COMBINATION TO CONTROL Ralstonia solanacearum ON POTATO PLANTED IN MIDDLE LATITUDE - Rosyidah, Anis; Wardiyati, Tatik; Abadi, Abdul Latief; Maghfoer, Moch. Dawam (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2013)
One of the common problems hampering the cultivation of potatoes in middle latitude is the presence of bacterium Ralstonia solanacearum commonly known to cause wilt disease, by which crop failure might be caused when serious attack occurs. The objectives of the research were to obtain the application of antagonistic microbes to inhibit the wilt disease caused by R.solanacearum and to increase the growth and yield of potato in middle latitude. The research was conducted from July to October 2012. Antagonistic microbes were used in this research to inhibit the bacterial wilt disease caused by R.solanacearum on potato planted in Bumiaji, Batu. Trichoderma viride, Streptomyces sp. and Pseudomonas fluorescens isolates were selected to be applied as treatments either singly or in combination. Randomised block design was applied on the treatment group with three replications. The results showed that the single application of Pseudomonas fluorescens or combined application of Streptomyces sp. and Trichodermaviride + Streptomycessp. was capable of extending incubation period 4 to 7 days and reducing disease incidence 44.85% - 50.09%, reducing disease intensity up to 61.23 - 72.77%, reducing the population R.solanacearum up to 7.28 - 97.88%, increasing the number of leaves and the marketable yield as much as 67.96 - 81.98%.Keywords: control, Ralstonia solanacearum, antagonistic microbes, middle latitude